THE IMAGE OF WOMEN IN HANINDAWAN'S LAMPOE PLENTHONG 15 WATT DRAMA SCRIPT - Tian Setyanto; Andayani Andayani; Nugraheni Eko Wardani (Universitas Negeri Makassar, 2021)
The purpose of this research was to describe the image of women in Hanindawan's drama script Lampoe Plenthong 15 Watt. This research was a descriptive qualitative research with content analysis. The data was from Hanindawan's Lampoe Plenthong 15 Wattdrama script. Data collection techniques used library techniques, listen and take notes. The data analysis technique used an interactive technique with a stylistic approach. Based on the results of the research, it was found that the form of women's image included the role of women as individuals, the role of women as mothers, the role of women as wives, the role of women as workers and the role of women in community life.